Case Report: Mucous Membrane Pemphigoid With IgG and IgA Anti-Laminin γ1 Antibodies and IgA Anti-Laminin α5 Antibodies - Kuang, Wenjing; Qian, Hua; Zhang, Qiyue; Li, Wei; Hashimoto, Takashi; Zeng, Xin; Li, Xiaoguang (Frontiers in Immunology, 2022)
Mucous membrane pemphigoid (MMP) and anti-laminin (LM) γ1 pemphigoid, two subtypes of subepidermal autoimmune bullous diseases characterized by autoantibodies against epidermal basement membrane zone proteins, mainly show mucosal and skin lesions, respectively. The known autoantigens of MMP includes BP180, BP230, LM332, integrin α6β4 and type VII collagen, and anti-LMγ1 pemphigoid targets LMγ1. In this study, we present an unique MMP case with oral mucosal lesions, which showed positive IgA signals on basement membrane zone in indirect immunofluorescence using normal human skin and on dermal side in indirect immunofluorescence using salt-split skin, positive IgA autoantibodies against LMγ1 by immunoblotting of epidermal extracts, positive IgA autoantibodies against LMα5 by immunoblotting of LM521 recombinant protein and positive IgG autoantibodies against LMγ1 by immunoblotting of LM111 and LM521 recombinant proteins at first visit (Day 0). After therapy, further serological analyses of serum samples collected at Day 30 and Day 50 indicated that IgA autoantibodies against LMγ1 were likely to be pathogenic. These results suggest that LMγ1 is another autoantigen of MMP, and our patient might be the first reported case of anti-LMγ1 MMP.